Anon is Not Dead: Towards a History of Anonymous Authorship in Early-Twentieth-Century Britain - Kopley, Emily (Mémoires du livre / Studies in Book Culture, 2016)
In 1940, Virginia Woolf blamed the printing press for killing the oral tradition that had promoted authorial anonymity: “Anon is dead,” she pronounced. Scholarship on the printed word has abundantly recognized that, far from being dead, Anon remained very much alive in Britain through the end of the nineteenth century. Even in the twentieth century, Anon lived on, among particular groups and particular genres, yet little scholarship has addressed this endurance. Here, after defining anonymity and sketching its history in the late nineteenth and early twentieth century, I offer three findings. First, women had less need for anonymity as they gained civil protections elsewhere, but anonymity still appealed to writers made vulnerable by their marginalized identities or risky views. Second, in the early twentieth century the genre most likely to go unsigned was autobiography, in all its forms. Third, on rare occasions, which I enumerate, strict anonymity achieves what pseudonymity cannot. I conclude by suggesting that among British modernist authors, the decline of practiced anonymity stimulated desired anonymity and the prizing of anonymity as an aesthetic ideal.